The performance and fitness standards in young Czech triathletes of both sexes - Horcic, J.; Bunc, V.; Heller, J.; Cingalek, R.; Slaba, R.; Podrouzek, R.; Podubecka, J. (2001)
The popularity of triathlon is increasing from year to year, the results is the inclusion of triathlons into the program at the Olympic games in Sydney 2000. The best young male and female Czech triathletes of were investigated longitudinally by the Faculty of P.E. and Sports in cooperation with Czech triathlon association. The 67 men (mean age = 17.6± 1.2 years, height = 179.2± 6.7 cm, body mass = 69.0± 6.6 kg) and 39 females (17.1± 1.6; 167.0± 3.5; 57.0± 4.2 ) was evaluated. These subjects were assessed in laboratory in the field in the years from 1995 to 1998. The subjects were evaluated according to age and gender. The mean values of assessed variables are following :